Development of a computer program for prestressed footbridge beams / Zulkepli Yahya - Yahya, Zulkepli (1989)
This computer aided design will compute the prestressed Footbridge beams using ultimate limit state and serviceability limit state analysis. The program was developed on the Mini Computer HP9000/840 using the Fortran 77 language. The output (i.e results) of the computer program are verified by manual calculation as in Appendix 3.